2013
DOI: 10.1063/1.4811517
|View full text |Cite
|
Sign up to set email alerts
|

Jahn-Teller effect in CH2DO/CHD2O(${\rm \tilde X}^{\rm 2} {\rm E}$X̃2E): Vibronic coupling of all vibrational modes

Abstract: For the Jahn-Teller active methoxy radical CH3O∕CD3O(X̃(2)E), only the degenerate vibrational modes break the C3v geometric symmetry. For the isotopologues CH2DO∕CHD2O, all their normal vibrational motions break the C3v geometric symmetry, which results in a splitting of the adiabatic potential energy surfaces (APESs), that is, all vibrational modes are Jahn-Teller active. Therefore, each fundamental vibrational energy level of CH2DO∕CHD2O splits into two levels due to a combination of Jahn-Teller and spin-orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Based on the calculated wave functions, we are able to assign these two levels as the spin-orbit components of the 6 2 states. This also seems consistent with the assignment of two levels of 1681 cm 1 and 1725 cm 1 to 6 2 states by Shao and Mo, 28 considering that the energy levels obtained by these authors generally lie higher in energy than the features in the SEVI spectra.…”
Section: B Computed Spectra and Assignment For Ch 3 Osupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the calculated wave functions, we are able to assign these two levels as the spin-orbit components of the 6 2 states. This also seems consistent with the assignment of two levels of 1681 cm 1 and 1725 cm 1 to 6 2 states by Shao and Mo, 28 considering that the energy levels obtained by these authors generally lie higher in energy than the features in the SEVI spectra.…”
Section: B Computed Spectra and Assignment For Ch 3 Osupporting
confidence: 91%
“…Although several notable and high-quality theoretical studies of methoxy have been reported, 26,27 the most elaborate investigations of the ground state are those carried out by Shao and Mo 28 and by Sibert and co-workers 12 using a quasidiabatic representation 29,30 parametrized by calculations carried out at the CCSD(T) 31 level of theory with correlation-consistent basis sets. 32 In particular, in the recent study of the matrix isolated infrared spectrum, 12 the vibrational assignments were facilitated by use of a model Hamiltonian whose eigenvectors can be inspected to reveal the quantum numbers and angular momentum of the states, to the degree that the former can be deduced.…”
Section: Introductionmentioning
confidence: 99%
“…Methoxy has also been a subject of numerous theoretical studies, some of these combining experimental with computational work. However, none has addressed the calculation of h 1 and h 2 .…”
Section: Resultsmentioning
confidence: 99%
“…43 Recently, this model has been successfully developed to calculate the vibronic energy levels of polyatomic molecules with C 3v symmetry. 39,40,[44][45][46][47][48][49][50] One of the key features of this method is that the diabatic potential energy surfaces are expressed by Taylor expansions with normal coordinates as variables. This method has been extended to linear molecule in previous work, which enables us to compute the spin-vibronic energy levels of linear BrCN + (X 2 Π).…”
Section: A Diabatic Modelmentioning
confidence: 99%